2017
DOI: 10.33736/ijbs.515.2016
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Supply Chain Linkage on Micro and Small Enterprises’ Performance

Abstract: The practice of linking the enterprises with their channel members through supply chain activities is meant to achieve better performance and to create a win-win situation for both sides. A study on supply chain linkages is necessary in order to observe the effect of the linkages on firms’ performance. Therefore, this study is conducted to examine the factors of supply chain linkages that affect the business performance among micro and small enterprises. Three factors were proposed, which are information shari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…Al respecto, [27] plantea que la mayoría de los microempresarios posee formación empírica especialmente proveniente de la tradición familiar en cuanto al trabajo. Resultan relevantes las aportaciones de [48] al exponer que no poseer personal profesional incide en el empirismo a la hora de gerenciar los procesos de la empresa, mermándose los niveles de productividad financiera y aumentando la brecha en las ventajas comparativas y competitivas inter e intra-sector [49]. La contratación de personal con un bajo nivel profesional pudiera solventarse con un mercado laboral amplio existente, aunque sólo un poco más de la mitad de los microempresarios trabaja con sueldos fijos, lo cual no pudiera resultar atractivo para dicho mercado [32].…”
Section: Discusión De Los Resultadosunclassified
“…Al respecto, [27] plantea que la mayoría de los microempresarios posee formación empírica especialmente proveniente de la tradición familiar en cuanto al trabajo. Resultan relevantes las aportaciones de [48] al exponer que no poseer personal profesional incide en el empirismo a la hora de gerenciar los procesos de la empresa, mermándose los niveles de productividad financiera y aumentando la brecha en las ventajas comparativas y competitivas inter e intra-sector [49]. La contratación de personal con un bajo nivel profesional pudiera solventarse con un mercado laboral amplio existente, aunque sólo un poco más de la mitad de los microempresarios trabaja con sueldos fijos, lo cual no pudiera resultar atractivo para dicho mercado [32].…”
Section: Discusión De Los Resultadosunclassified
“…information system availability plays an important role in connecting between customers and providers (Man, 2006). The nature of the information provided should help customers to easily choose products, either information provided offline or online (Liang, 2008;Ya'kob & Jusoh, 2016). The Supplier shall ensure that the information provided is sufficient for the consumer, correct and assured of its content (Chen & Wells, 2000).…”
Section: Halal Supplier Service Qualitymentioning
confidence: 99%
“…Choi, 2010;Yigitbasioglu, 2010). However, there are other studies that do not differentiate with which partner the information is exchanged (Bellamy et al, 2014;Hult et al, 2004Hult et al, , 2007Ya'kob and Wan Jusoh, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Information shared with customers/suppliers and performance Many studies have demonstrated the need for inter-organisational and bidirectional information exchange so that the supplier-buyer relationship is successful (Gligor and Autry, 2012;Lotfi et al, 2013;Marinagi et al, 2015;Ya'kob and Wan Jusoh, 2016). Thus, the exchange of information is a way of coordinating the independent actors (the focal firm, its customers and its suppliers) to work together in order to gain the common goal of improved chain performance (Simatupang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation